KEMAMPUAN MENENTUKAN UNSUR-UNSUR INTRINSIK CERITA RAKYAT SISWA KELAS X SMA NEGERI 2 BUKIT BATU KABUPATEN BENGKALIS - Kurniati, Dira; Mustafa, M. Nur; Razak, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study discusses the ability to determine the intrinsic elements of folklore of the class X students of SMA Negeri 2 Bukit Batu Bengkalis Regency, which is analyzed with quantitative methods. In this study, there is a problem formulation that examines the level of ability to find the intrinsic elements of folklore class X students of SMA Negeri 2 Bukit Batu and the different ability levels of each class. This study aims to determine the level of ability to determine the intrinsic elements of folklore student SMAN 2 Bukit Batu. Source of the data that has been the subject of this research are the students of class X SMA Negeri 2 Bukit Batu Bengkalis Regency. The research method used is a quantitative method that describes the calculated data processed by statistical counting. Data collection techniques in this study is a questionnaire questionnaire technique. While the data analysis technique used uses statistical counting, data presentation and withdrawal of the final conclusion. The data from this study was 95 samples consisting of 24 samples from class XA, 25 samples from class XB, 25 samples from class XC and 21 samples from class XD. The aspects examined in this study are the essential elements of folklore, which consist of themes, characters, characterizations, plot, background, view, and message.Keywords: Ability to determine intrinsic elements folklore, students class X SMA 2 BukitBatu Bengkalis Regency.